2012
DOI: 10.5455/vetworld.2012.682-684
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of dermatophytosis in canine cases presented at Apollo Veterinary College, Rajashtan, India

Abstract: Aim: Ring worm are fungal infection relevant to animal and human health. The study was aimed to assess the frequency of dermatophytes infection of the skin of dogs in and around the Jaipur city. Materials and methods: One twenty canine samples were obtained during three years (2008)(2009)(2010)(2011) from dogs suffering from different dermatological disorders and were invitro processed for dermatophytes detection at the Department of Microbiology, Apollo College of veterinary medicine Agra Road, Jaipur. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
2
9
0
1
Order By: Relevance
“…[ 15 ] and Gangil et al . [ 21 ] are also in full agreement with the age group distribution of human isolates as noticed in this study that the adult human owners (of 21-30 years of age) were mostly affected as they remain more closely attached with their pets (whether infected or healthy) than the older ones or younger ones, resulting in a higher exposure to infection also. Authors such as Maraki et al .…”
Section: Discussionsupporting
confidence: 90%
“…[ 15 ] and Gangil et al . [ 21 ] are also in full agreement with the age group distribution of human isolates as noticed in this study that the adult human owners (of 21-30 years of age) were mostly affected as they remain more closely attached with their pets (whether infected or healthy) than the older ones or younger ones, resulting in a higher exposure to infection also. Authors such as Maraki et al .…”
Section: Discussionsupporting
confidence: 90%
“…Lesions in cases of dermatophytosis are variable for each species of animal [ 1 , 24 - 26 ], the most common clinical symptoms being hair loss, skin crust, erythema, and pruritus (Figures- 3 and 4 ). Other studies showed that dermatophyte infection in dogs cause lesions localized to the face, legs, and/or tail [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Murmu et al in a previous study isolated in 16.7% from dogs' hair, skin and nails with suggestive lesions of dematophytoses [32]. In India Gangil et al, isolated T. mentagrophytes in 18.3% from dogs with skin lesions [33], while in Baghdad, Jasim isolated 30.95% in dogs, from samples taken from various body sites [34].These data contrast with our findings as we found a lower frequency that the previously cited authors, but this finding becomes relevant as it can be a source of infection or re-infection in human and animals, so better hygienic conditions are recommended to dogs´ owners as well as in places where animals are too close to each other (aesthetic canines and veterinary clinics).…”
Section: Discussionmentioning
confidence: 99%